Odpowiedzi

  • Użytkownik Zadane
2010-03-02T18:15:33+01:00
{x+y-4=0
3x-y=0

x+y=4
3x-y=0

4x=4//4
x=1








{x+y-3=0
x-2y-2=0

x+y=3/*2
x-2y=2

2x+2y=6
x-2y=2

3x=8//3
x= 8/3



{2x+y=3
-2x+y=2 /*(-1)

2x+y=3
2x-y=-2

4x=1/4
x=1/4



16 4 16
  • k666
  • Początkujący
2010-03-02T18:16:21+01:00
Pierwsze
y =3x
y+x=4x
4x-4=o
4x= 4
x =1
y=3
drugie
x+y=3
x=y+2
2y +2 =3
2y=1
y=0,5
x=2,5
trzecie
4x=1
x=0.25
y=2,5
(:
5 3 5
2010-03-02T18:23:56+01:00
{x+y-4=0
3x-y=0

x+y=4/razy -3
3x+y=0

-3x-3y=-12
3x+y=0

-2y=-12/:(-2)
y=6
3x-6=0
3x=6/;3
x=2
y=6



b)
{x+y-3=0
x-2y-2=0

x+y=3/razy 2
x-2y=2

2x+2y=6
x-2y=2
3x=8/:3
x=2,6

2,6+y-3=0
y=-2,6+3
y=0,4


c)
{2x+y=3
-2x+y=2
2y=5/:2
y=2,5
2x+2,5=3
2x=3-2,5
2x=0,5/:2
x=0,25





5 3 5